Multicolour nanoscopy of fixed and living cells with a single STED beam and hyperspectral detection - Winter, Franziska Ruth; Hell, Stefan (Scientific reports, 2017)
The extension of fluorescence nanoscopy to larger numbers of molecular species concurrently visualized by distinct markers is of great importance for advanced biological applications. To date, up to four markers had been distinguished in STED experiments featuring comparatively elaborate imaging schemes and optical setups, and exploiting various properties of the fluorophores. Here we present a simple yet versatile STED design for multicolour imaging below the diffraction limit. A hyperspectral detection arrangement (hyperSTED) collects the fluorescence in four spectral channels, allowing the separation of four markers with only one excitation wavelength and a single STED beam. Unmixing of the different marker signals based on the simultaneous readout of all channels is performed with a non-negative matrix factorization algorithm. We illustrate the approach showing four-colour nanoscopy of fixed and living cellular samples.
Gesehen am 25.10.2018